Ni Krining, Antara Pengorbanan dan Perlawanan dalam Budaya Patriarki Bali - Khothibul Umam (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
A literature is a reflection of real world reality. A writer wrote it in a literary work. One of the themes of short stories in Indonesia is the theme of women's resistance in traditional and cultural circles. The short story "The First Night of a Priest" by Gde Aryantha Soethama tries to offer the theme. The main character in the short story is Ni Krining, a Balinese woman from a lower caste who is married to a Brahman caste. The situation makes Ni Krining must accept polygamy. Behind his sacrifice, Ni Krining has resisted the cultural system in his environment and made his existence recognized. This study uses an existentialist feminism study to explore various reasons that make Ni Krining gain recognition in its environment which is dominated by patriarchal culture.